The patient's perception of the role of prayer in the family practice consultation : a qualitative study conducted in the Western Cape - Liddle, Alfred Sydney (Department of Public Health and Family Medicine, 2017)
Prayer and spirituality are aspects of patient care that are not often addressed in modem medical practice. Controversy surrounds the family practitioner's role regarding prayer. The patient's belief system and religion are neglected psychosocial variables. Prayer is accepted as an integral aspect of therapeutic counselling, by pastoral counsellors. This is a qualitative study of a purposeful sample of 10 adult patients, selected by the author and three other family practitioners of different religious persuasions. All the participating doctors practise in the "township" areas of the Cape Peninsula. The intention is to gauge the patients' opinion on the family doctors' role regarding prayer and to determine whether differences in religion between the doctor and patient affects the patients' choice of doctor or their religious enquiry or discussion. The individual semi structured interviews are summarised in Venn diagrams. Results, after analysis, are presented collectively. The results confirm other studies and literature, viz. that there is a lack of religious inquiry, initiated by doctors. All respondents had, however, indicated that they would attend doctors of different religious persuasions. Most respondents felt that they would not discuss religious or spiritual issues and would only attend those practitioners for biomedical needs. The positive reinforcement of the doctor patient relationship, for respondents who shared spirituality or prayer with their practitioners, is a significant finding. A sample spiritual inquiry and respondents' suggestions to facilitate the introduction of spirituality into the family practice consultation are presented.